Influence of Water on Enzymatic Esterification of Racemic Ketoprofen with Ethanol in a Solvent-Free System - Toledo, Victoria; Llerena Suster, Carlos Rafael; Ruscitti, Claudia Beatriz; Collins, Sebastián Enrique; Briand, Laura Estefania (Topics in Catalysis)
The effect of water added in the kinetic resolution of rac-ketoprofen with ethanol catalyzed with Candida antarctica lipase B was investigated under reaction conditions and at a molecular level. The reaction was performed at 45 oC for 24 h with the commercial biocatalyst known as Novozym 435. The addition of water from 0.5 to 10 % v/v to the reaction medium enhances the specific activity (from 2 to 4 micromol.mg-1.h^-1), enantiomeric ratio E (1 towards 5), enantiomeric factor EF (0.1 towards 0.5) and the enantiomeric excess towards dexketoprofen (above 50%). At a molecular level, the rate of H/D isotopic exchange of the amide hydrogen of the lipase B of Candida antarctica demonstrated that the enzyme exposed to dehydrated ethanol possesses highly flexible sites (45% of the sites are exchanged with a rate of 30 min^-1) and the addition of water diminishes the rate of H/D exchange altering the flexibility (the exchange rate falls down to 2.7 - 0.06 min^-1). Additional studies on the secondary structure suggest that the beta-sheet structure lead to slowest exchange H-amide sites. Fil: Toledo, Victoria. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Ciencias Aplicadas "Dr. Jorge J. Ronco". Universidad Nacional de la Plata. Facultad de Ciencias Exactas. Centro de Investigación y Desarrollo en Ciencias Aplicadas; Argentina Fil: Llerena Suster, Carlos Rafael. Universidad Nacional de La Plata. Facultad de Ciencias Exactas. Departamento de Ciencias Biológicas. Laboratorio de Investigación de Proteínas Vegetales; Argentina Fil: Ruscitti, Claudia Beatriz. Universidad Nacional de La Plata; Argentina Fil: Collins, Sebastián Enrique. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Santa Fe. Instituto de Desarrollo Tecnológico para la Industria Química. Universidad Nacional del Litoral. Instituto de Desarrollo Tecnológico para la Industria Química; Argentina Fil: ...